(3OjhGf GdCHjhQOj (B((3bSe GdYQGbjGJ(B)s - (3CHhGdeXaQ eMeO Hf CMeO Hf eMeO Hf eYGhjI GdCUZQ GdCehj GdCHjhQOj,J (B557 (3g` s ((3CHhHcQ Hf TQa TGg s)
(3ChdgG (B:s
(3CeG HYO MeO Gddg Ydi fYeI ZfGA GdeQGO, hefMI eJUdI GdEeOGO, aEf GdTYQ OjhGf GdYQH, hJQLeGf GdCOH, hbO Qhi Cfg HefRdI GdcdGe s
(3BNQgG (B:s
(3YLHJ ef GKfjf GSJVjYG hCLMaJ HbOQ QHgeG CjOj GdNWhH GdahGOM ef GHf cQje de JUHg NUGU hef Cfhj ddCQGRd eGOM s
(3GfXQ GdLRA GdChd HQbe (B599 (3COH HYfhGf GdYQGbjGJs
(3hjdjgG fbhd TYQjI aj KdGK hQbGJs
(3hHChdgG JQLeI ddCHjhQOj ef hajGJ GdCYjGfs
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdCOHs